Optimisation and Constraint Based Heuristic Methods for Advanced Planning and Scheduling Systems - Ornek, Arslan; Ozturk, Cemalettin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
Manufacturing Resources Planning (MRPII) systems are unable to prevent capacity problems occurring on the shop floor such as varying workloads, changing bottlenecks, high Work-in-Process (WIP) levels, lower machine utilisation, less throughput, late deliveries that cannot be resolved easily in the short term because production scheduling is based on fixed lead times and backward scheduling logic. For this reason, a new breed of concepts called APS (Advanced Planning and Scheduling) systems emerged which include finite capacity planning at the shop floor level through constraint based planning. In this paper, we present a Constraint Programming (CP) model to show how optimisation models could be used in this context. We also present a two phase heuristic to solve this complicated APS problem. While jobs are assigned to the best eligible machines to smooth the workload on the machines in the first phase, a constraint based scheduling heuristic schedules jobs once they are assigned to eligible machines in the second phase. We provide numerical tests and discuss the results for both models and the heuristic. The concluding remarks and suggestions for future research are stated in the final section of the paper.